Effect of dietary incorporation of neem (Azadirachta indica) leaf powder on growth and life-table characteristics of red flour beetle, Tribolium castaneum* - GUPTA, SUDHAKAR (The Indian Journal of Agricultural Sciences, 2011)
The present study revealed that dietary incorporation of neem leaf powder did not alter the growth ofhead capsule of red flour beetle, T. castaneum. Higher levels (2%) of leaf enhanced the mortality of the egg, fourth and sixth instar larval stages. The dry weights ofthe latter larval (fourth and sixth instar larvae) stages, pupal and adult stages significantly declined while their tissue water contents increased. Similarly, the absolute growth rate of immature and adult stages also severely declined at 2% treatment.